2013
DOI: 10.1210/jc.2012-4322
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Need for Fixation of Atypical Femoral Fracture

Abstract: About one-half of incomplete atypical femur fractures required surgical intervention, and subtrochanteric involvement could be used as a predictor of the requirement for fixation in these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Focal marrow, endosteal, or periosteal edema may be seen at MR imaging. Subtrochanteric fracture location has also been shown to correlate with the ultimate need for surgical fixation (73), although the literature is inconclusive. Close clinical and imaging surveillance during a trial of conservative therapy may be used in minimally symptomatic patients, although prophylactic fixation of incomplete fractures is most often used due to the high failure rate of conservative therapy (70).…”
Section: Figure 24mentioning
confidence: 99%
“…Focal marrow, endosteal, or periosteal edema may be seen at MR imaging. Subtrochanteric fracture location has also been shown to correlate with the ultimate need for surgical fixation (73), although the literature is inconclusive. Close clinical and imaging surveillance during a trial of conservative therapy may be used in minimally symptomatic patients, although prophylactic fixation of incomplete fractures is most often used due to the high failure rate of conservative therapy (70).…”
Section: Figure 24mentioning
confidence: 99%
“…Lin et al [22] reported that mean union time after surgical nailing for AFFs was shorter (mean, 4.5 months; range, 4-5 months) for four fractures with discontinuation of alendronate and administration of boneforming agents (TPTD for one fracture; strontium ranelate for three fractures) than for six fractures with continuation of alendronate after surgery (mean, 23.5 months; range, 18-31 months). TPTD has also been suggested as a nonsurgical intervention for AFF [14,16]. Chiang et al [13] reported that TPTD use was associated with increased bone remodeling in patients with AFF.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial suggested a role for TPTD in accelerating healing for fractures of the distal radius in postmenopausal women [12]. TPTD is, thus, expected to see use in the treatment of AFF [13,14]. Recent sporadic case reports and case series have associated discontinuation of bisphosphonate therapy and initiation of TPTD treatment with healing of AFFs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a market size that is substantially less than most quaternary centers, we were able to evaluate, and more importantly, treat a significant number of these fractures. Lee et al 29 reported on 51 patients with 65 incomplete fractures seen at four different tertiary centers during a similar time period (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). This adds to the evidence that as the number of patients receiving bisphosphonates increases in our communities, a parallel increase in the incidence of these fractures should be expected to present to tertiary care facilities.…”
Section: Discussionmentioning
confidence: 99%